Prognostic significance of the platelet-to-lymphocyte ratio in ovarian cancer: a meta-analysis - Xu, Weiyu; Wang, Wenqin; Yang, Min; Song, Lina; Xiong, Jianping; Lin, Jianzhen; Long, Junyu; Bai, Yi; Zheng, Yongchang; Zhao, Lin; Sang, Xinting; Zhao, Haitao (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Background: Recent studies have shown that the pretreatment measurement of the peripheral platelet-to-lymphocyte ratio (PLR) is an independent predictor of poor prognosis of various types of malignancies. However, the relationship between the pretreatment PLR and the prognosis of ovarian cancer remains largely undefined. A meta-analysis was conducted to investigate the prognostic significance of PLR in patients with ovarian cancer. Methods: We searched the PubMed, Embase and Web of Science databases to collect eligible studies, followed by application of STATA version 12.0 for statistical analysis. Results: Eight studies enrolling 1,636 patients were ultimately included in this meta-analysis. As a result, an elevated PLR was significantly correlated with poor OS [hazard ration (HR) =5.95, 95% confidence interval (CI): 4.35–8.14, P=0.000] in patients with ovarian cancer. Moreover, subgroup analyses revealed that an elevated PLR was able to predict poor OS when the cut-off value was near 200 (HR =6.78, 95% CI: 4.50–10.21, P